Peranan Kekuatan Pasar dalam Penetapan Harga dan Kemajuan Teknologi - Adelia Ananda Putri; Elok Fadinda; Saefi Anissaturrohmah; Zalfa Qonita; Naerul Edwin Kiky Aprianto (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Market power refers to a company's ability to influence the price of goods or services in the market. In a perfectly competitive market, both buyers and sellers have set prices, therefore businesses can set their prices without affecting the market price. In contrast, in less pure market structures such as oligopoly or monopoly, businesses can set prices and influence the market. When businesses with strong market power outperform new competitors, it constrains consumer purchasing power and allows businesses to set prices and improve product quality. In addition, technology plays an important role in production efficiency, as innovation can lower costs and create new products that meet consumer needs. The purpose of this study is to analyze the role of market forces in pricing and technological advances and provide important implications for producers to determine the price of goods and services. This research uses a qualitative approach combined with a literature review approach to analyze data related to the main topic of research. The data comes from secondary literature, which includes books, scientific journals, and articles. The study found that high market concentration, where a few large firms dominate, often leads to less competition and increased market power for those firms. This can lead to higher prices, lower quality, and less innovation.